Difference analysis of long drive swing mechanical movement towards ball velocity based on analysis kinematics approach between skill and unskill golf player - Rusdiana, Agus; Sartono, Hadi; Nurjaya, Dede Rohmat; Syahid, Angga M (Universitas Nusantara PGRI Kediri, 2019)
The purpose of this study was to find out the differences in swing mechanical movement long drives towards the ball velocity based on the kinematics analysis approach between skills and unskilled golf players. The kinematic variables analysis consists of trunk forword tilt, club stick velocity, knee flexion, wrist hinge at the top, leading arm angle, lateral band, hip rotation dan shoulder rotation. The method used in this research is quantitative descriptive method, while the data analysis technique uses the average difference test analysis.The sample in this study were 2 trained and 4 amateur athletes in the Indonesian Education University of UPI Bandung, with an average of height 1.63 ± 2.4 m, Body mass 72.4 ± 3.6 kg and Age 37.4 ± 7.6 years. The results of this study indicate that of the ten kinematics variables analyzed there were four indicators which showed significant differences in the level of alpha 0.05 including club speed at impact (t = 0.007), lateral band after impact ball (t = 0.006), shoulder rotation (t = 0.005) and non dominant dominant flexion at elbow joint arm (t = 0.003).